TU2.2 Endo-Sponge Carries Good Outcome for Low Rectal Anastomotic Leak; Case Series study. (9th August 2022) - Ahmed, Salma; Abbakar, Malaz; Hassan, Karim; Mohammed, Mohammed; Magee, Conor; Wilson, Jeremy
Abstract: Introduction: Rate of anastomotic leak is considered rare, and the low rectal ones are approximately 10% of all leaks. Management of anastomotic leak is variable and could be challenging. ENDO-SPONGE is advised by experts to be considered given some criteria to be met but in general, ENDO-SPONGE is thought to improve patients' life quality and maintains the possibility of stoma reversal after resolution of the leak. Objective: To assess the management of anastomotic leak using ENDO-SPONGE in our hospital and to compare our practice with the international published data. Methods: Case study of patients diagnosed with anastomotic leak and treated with ENDO-SPONGE. All cases from 2016 to 2021 were included. Concordance with the NICE briefing and recommendation which was published in 2019 was studied. All data were collected in a Microsoft forms then transcribed into an Excel sheet. Results: 13 patients treated with ENDO-SPONGE were identified – median age is 66. Guidelines suggest that ENDO-SPONGE changes should occur within 24–72 hours and the compliance from the trust was only 25%. However the compliance with the number of changes, place of insertion, and the outcome was 100%. 99% of the ENDO-SPONGE replacement took place in the theatre, only one patient's ENDO-SPONGE was replaced in endoscopy department. Complete resolution of the leak occurred in 11 of the 13 patients and only 2 required open drainage. 5/13 were eventually reversed. Conclusions: More Compliance with timing of replacement of ENDO_SPONGE should be improved but overall ENDO_SPONGE carried a good outcome with complete resolution in nearly 85% of patients.